1993
DOI: 10.1111/j.1600-0668.1993.t01-1-00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Responses To Environmental Tobacco Smoke From Tobacco-Burning And Tobacco-Heating Cigarettes

Abstract: Sensory ratings, respiratory behavior and eye blink rate were recorded in 11 nonsmokers exposed to a no‐smoking (CONTROL) condition or to environmental tobacco smoke (ETS) from one of three kinds of cigarettes: a Kentucky reference (1R4F), an ultra‐low tar (ULT) and one that heats tobacco (TEST).For each two‐hour session in a controlled‐environment room, two smokers “puffed” unlit cigarettes, for the CONTROL condition, or smoked 16 cigarettes to generate ETS (sidestream plus exhaled mainstream smoke). Concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Our eye blink rate (a response not included in the work by Cain and colleagues) results are consistent with previous work using SS (Muramatsu et al, 1983) and ETS (Winneke et al, 1984;Kay et al, 1990;Walker et al, 1993). We observed that eye blink rate was significantly elevated for only the highest ETS-RSP concentration, although some eye irritation was perceived with much lower levels.…”
Section: Ets-rsp Conc (Pg1m3)supporting
confidence: 92%
See 4 more Smart Citations
“…Our eye blink rate (a response not included in the work by Cain and colleagues) results are consistent with previous work using SS (Muramatsu et al, 1983) and ETS (Winneke et al, 1984;Kay et al, 1990;Walker et al, 1993). We observed that eye blink rate was significantly elevated for only the highest ETS-RSP concentration, although some eye irritation was perceived with much lower levels.…”
Section: Ets-rsp Conc (Pg1m3)supporting
confidence: 92%
“…ETS levels significantly different from the CONTROL condition are denoted by filled symbols. The general pattern is consistent with recent findings from this laboratory (Walker et al, 1993) in that reduced breathing frequency but no change in minute ventilation, occurred during ETS exposure. Comparison of the second and third panels of Figure 8 demonstrates that this was accomplished primarily by increases in expiratory time, which showed the greatest percentage change.…”
Section: Respiratory Responsessupporting
confidence: 91%
See 3 more Smart Citations